Trends in Statin Use Among US Adults With Chronic Kidney Disease, 1999–2014. Issue 2 (22nd January 2019) - Mefford, Matthew T.; Rosenson, Robert S.; Deng, Luqin; Tanner, Rikki M.; Bittner, Vera; Safford, Monika M.; Coll, Blai; Mues, Katherine E.; Monda, Keri L.; Muntner, Paul
Abstract : Background: The 2013 American College of Cardiology/American Heart Association cholesterol guidelines recognize cardiovascular disease and diabetes mellitus but not chronic kidney disease (CKD) as high‐risk conditions warranting statin therapy. Statin use may be lower for adults with CKD compared with adults with conditions that have guideline indications for statin use. Methods and Results: We analyzed data from the National Health and Nutrition Examination Surveys from 1999–2002 through 2011–2014 to determine trends in the percentage of US adults ≥20 years of age with and without CKD taking statins. CKD was defined by an estimated glomerular filtration rate <60 mL/min per 1.73m 2 or albumin‐to‐creatinine ratio ≥30 mg/g. Statin use was identified through a medication inventory. Between 1999–2002 and 2011–2014, the percentage of adults taking statins increased from 17.6% to 35.7% among those with CKD and from 6.8% to 14.7% among those without CKD. After multivariable adjustment, adults with CKD were not more likely to be taking statins compared with those without CKD (prevalence ratio, 1.01; 95% CI] 0.96–1.08). Among adults without a history of cardiovascular disease, those with CKD but not diabetes mellitus were less likely to be taking statins compared with those with diabetes mellitus but not CKD (prevalence ratio, 0.54; 95% CI, 0.44–0.66). Among adults with a history of cardiovascular disease, there was no difference in statin use between those with CKD but not diabetes mellitus versus those with diabetes mellitus but not CKD (prevalence ratio, 0.95; 95% CI, 0.79–1.15). Conclusions: CKD does not appear to be a major stimulus for statin use among US adults.